Horizontally polarized shear waves in stratified anisotropic (monoclinic) media - Ilyashenko, A.V.; Kuznetsov, S.V. (Archives of Mechanics, 2018)
The dispersion relations are derived for the horizontally polarized shear (SH) waves in stratified anisotropic plates with arbitrary elastic anisotropy. Analytical expressions for the vectorial group and ray velocities of SH waves propagating in anisotropic layers with monoclinic symmetry are obtained. Closed form relations between velocities and specific kinetic and strain energy for SH waves are derived and analyzed.